Analysis of the impact of quizizz-based learning, and learning facilities in increasing student learning motivation: integration with SDG. - Ihsan, Muhammad Zidan Nur; Maksum, Muh. Nur Rochim; Istanto, Istanto; al Irfani, Sofiy Zaini (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3742, 2025)
The low motivation of students to learn in Indonesia is still a major problem in the world of national education. This condition causes a decline in the quality of education, which will ultimately hinder the achievement of Sustainable Development Goal 4 (SDG 4), namely quality and sustainable education. Therefore, this study was conducted to analyze factors that can increase student learning motivation, especially the influence of learning facilities and the use of the Quizizz application in the learning process. This study uses a quantitative approach and Structural Equation Modeling (SEM) analysis. The research sample consisted of 199 students of Muhammadiyah PK Surakarta Junior High School (SMP) who were selected using purposive sampling techniques. The results of this study showed that learning facilities had a significant effect on learning motivation by 47.9% (β:0.479 P-Value 0.002). In addition, the use of the Quizizz application also had a significant effect of 31.1% (β:0.311 P-Value 0.046). Thus, it can be concluded that the learning facilities and the use of the Quizizz application have an influence on students' learning motivation. The combination of the two is needed to increase students' learning motivation optimally, so that the SDG4 goals regarding quality education can be realized.